Evaluation of half sib progenies of Ailanthus triphysa (Dennst.) Alston for early growth - Lalnunpuia, Jes; Santhoshkumar, A.V.; Hrideek, T.K.; Anoop, E.V.; Elizabeth P., Manju (Indian Journal of Agroforestry, 2021)
Half sib progenies of 30 plus trees of Ailanthus triphysa, selected from different parts of Kerala were evaluated for its genetic variability, heritability of morphological and physiological characters for genetic superiority. The nursery performance of the progenies of plus trees showed significant differences in collar diameter, the number of leaves and biovolume. However, the height of the seedling showed no significant variation. The progenies significantly differed in terms of physiological traits such as photosynthetic rate, stomatal conductance, transpiration rate, leaf temperature and relative water content. Moderate heritability was observed for morphological characters like the number of leaves (64 %), biovolume (50 %) and collar diameter (40 %) while, high heritability was observed for all the physiological traits. High heritability values indicate that all these characters were subjected to strong genetic control and can be inherited to the next generation. Among the morphological traits, the highest genetic gain (26.60) was observed in biovolume and the least value (2.35) was observed in seedlings height. The progenies FCV-AT-21, FCV-AT-33, FCV-AT-36, FCV-AT-37, and FCV-AT-40 were found superior based on overall mean performance. These trees can be recommended for further improvement programmes in this species.